‘Ring-Walking’ Aryl Cross-Coupling Reactions Involving Palladium Aryne Intermediates - Bayer, Eva A.; Sekiguchi, Yoshiya; Onnuch, Polpum; Liu, Richard Y. (Synlett, 2025)
The regiospecificity of conventional cross-coupling reactions, though advantageous for its predictability and retrosynthetic simplicity, constrains chemical-space exploration. Discovery efforts have become biased toward examining substitution patterns for which coupling partners are readily obtainable. To address this problem, we have developed a migratory (‘ring-walking’) cross-coupling approach that integrates the isomerization of arylpalladium(II) intermediates into catalytic cycles. A reversible isomerization was achieved through ligand design and the use of cesium fluoride as the base, and this process was then combined with a dynamic kinetic resolution of the regioisomeric aryl halides with a broad range of oxygen- and nitrogen-centered nucleophiles. The method permits rapid access to meta-substituted arenes from para-substituted electrophiles. This account summarizes the key mechanistic principles established during the development of these reactions.
Keywords: cross-coupling; Curtin–Hammett; isomerization; ring-walking; transition-metal catalysis